2002
DOI: 10.1103/physrevb.66.035110
|View full text |Cite
|
Sign up to set email alerts
|

Correlation gap in the heavy-fermion antiferromagnetUPd2Al3

Abstract: The optical properties of the heavy-fermion compound UPd 2 Al 3 have been measured in a frequency range from 0.04 to 5 meV (0.3-40 cm Ϫ1 ) at temperatures 2 KϽTϽ300 K. Below the coherence temperature T* Ϸ50 K, a hybridization gap opens around 10 meV. As the temperature decreases further (Tр20 K), a wellpronounced pseudogap of approximately 0.2 meV develops in the optical response; we relate this to the antiferromagnetic ordering which occurs below T N Ϸ14 K. The frequency-dependent mass and scattering rate giv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 79 publications
2
43
0
Order By: Relevance
“…First, the resistivity from 2 K up to 6.2 K (where a plot of In an earlier study [30], the temperature dependence of the DC resistivity of a thin film UPd 2 Al 3 was analyzed using a different expression and the gap was estimated to be 1.9 meV, larger than our value.…”
Section: Resistivity and Magnetic Susceptibilitymentioning
confidence: 67%
“…First, the resistivity from 2 K up to 6.2 K (where a plot of In an earlier study [30], the temperature dependence of the DC resistivity of a thin film UPd 2 Al 3 was analyzed using a different expression and the gap was estimated to be 1.9 meV, larger than our value.…”
Section: Resistivity and Magnetic Susceptibilitymentioning
confidence: 67%
“…Specifically optical studies have provided experimental access to the hybridization strength via direct observation of the hybridization gap ͑⌬͒ in the dissipative part of the optical conductivity ͓ 1 ͔͑͒. [7][8][9][10][11][12][13][14] These studies have also extensively verified the prediction of the PAM on the scaling between the hybridization gap and the effective mass: ͑ ⌬ T Coh ͒ 2 ϰ m * , where T Coh is the temperature below which coherent scattering between magnetic sites emerges. 8 There have also been recent studies of numerous Yb and Ce compounds, that have demonstrated a scaling between the size of ⌬ and T K , the Kondo temperature.…”
Section: Introductionmentioning
confidence: 92%
“…Such behavior is observed in many other heavy-fermion materials. [17,20,21,22] The m * (ω)/m 0 enhancement with decreasing temperature is accompanied by a formation of a broad peak in 1/τ (ω) in the energy region where the pseudogap-like suppression of σ(ω) appears as shown in Fig. 3b.…”
mentioning
confidence: 94%